2022
DOI: 10.3389/fphys.2022.837634
|View full text |Cite
|
Sign up to set email alerts
|

No Differences Between 12 Weeks of Block- vs. Traditional-Periodized Training in Performance Adaptations in Trained Cyclists

Abstract: The purpose of this study was to compare the effects of 12 weeks load-matched block periodization (BP, n = 14), using weekly concentration of high- (HIT), moderate- (MIT), and low- (LIT) intensity training, with traditional periodization (TP, n = 16) using a weekly, cyclic progressive increase in training load of HIT-, MIT-, and LIT-sessions in trained cyclists (peak oxygen uptake: 58 ± 8 ml·kg−1·min−1). Red blood cell volume increased 10 ± 16% (p = 0.029) more in BP compared to TP, while capillaries around ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“… 31 , 32 However, a recent study showed similar improvements between block and traditional periodization over 12 week in trained cyclists. 33 This is line with the case study of Solli and colleagues, 34 reporting that the world's best cross‐country skier succeeded using both traditional and block periodization during her career. In the present study, the three cyclists seem to adopt block periodization caused by the choice of secondary goals and preparation races before the Giro d'Italia.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“… 31 , 32 However, a recent study showed similar improvements between block and traditional periodization over 12 week in trained cyclists. 33 This is line with the case study of Solli and colleagues, 34 reporting that the world's best cross‐country skier succeeded using both traditional and block periodization during her career. In the present study, the three cyclists seem to adopt block periodization caused by the choice of secondary goals and preparation races before the Giro d'Italia.…”
Section: Discussionsupporting
confidence: 73%
“…A series of studies of Rønnestad and colleagues showed that high‐intensity block periodization leads to superior improvement in well‐trained cyclist when compared with high‐intensity evenly distributed across 4–12 weeks 31,32 . However, a recent study showed similar improvements between block and traditional periodization over 12 week in trained cyclists 33 . This is line with the case study of Solli and colleagues, 34 reporting that the world's best cross‐country skier succeeded using both traditional and block periodization during her career.…”
Section: Discussionmentioning
confidence: 99%
“…Zwift (Zwift Inc., Long Beach, CA, USA), a bicycle simulation software, and a roller fixture (Tacx NEO T2 Smart Trainer, Garmin Korea Ltd., Seoul, Republic of Korea) were used to eliminate external factors that might affect the research results, such as weather, wind, traffic, and road conditions, and to provide the same cycling environment [ 28 , 29 ]. The cumulative altitude per 10 km cycling was 62 m, the longest uphill section was 1.5 km, and the cumulative altitude was 18 m. The participants cycled 10 km each during the first and second cycling sessions.…”
Section: Methodsmentioning
confidence: 99%
“…The start of the block-periodized training intervention took place in the third week of the participant’s first trimester ( Figure 1 ). As part of the training intervention, she completed 12 weeks of structured cycling training as previously described ( Almquist et al, 2022 ). The structured training consisted of; four moderate-intensity interval training sessions (4 × 12 min) in week 1, three to six low-intensity training sessions (>60 min continuous cycling) in week 2, and four high-intensity interval training sessions (5 × 5 min) in week 3.…”
Section: Methodsmentioning
confidence: 99%
“…During a previous training intervention ( Almquist et al, 2022 ), in which the effects of periodized endurance training (cycling; 74%, XC-skiing/running; 24%, resistance training 2% of the sessions) were investigated, one of the female participants became pregnant during the intervention period. This participant wanted to complete the training intervention (see ethical considerations discussed below), which provided a unique data set on the haematological and physiological changes occurring during pregnancy and postpartum in a well-trained female cyclist in relation to maintained endurance exercise training.…”
Section: Introductionmentioning
confidence: 99%